Narrativas sobre a matemática escolar produzida por alunos de um curso noturno de educação de jovens e adultos - Castro, Luís Roberto Cezar de (Universidade do Vale do Rio do Sinos, 2006)
The purpose of this dissertation is to analyze narratives on School Mathematics, produced by students in Basic Education in evening school within a Program for the Education of Youths and Adults, at Escola Carlos Antonio Wilkens, a school located in the Veranopolis neighborhood, in the county of Cachoeirinha, state of Rio Grande do Sul, Brazil. The theoretical contributions of the research are ideas in the field of Education of Youths and Adults, in Ethnomathematics and Cultural Studies, examined from a perspective that is in line with postmodern thinking.The dissertation is organized in five chapters. In the first there is an overview of the research, explicating the theoretical position from which the study was performed, the report problematizing how the object of research was constructed, as well as methodological procedures. The second chapter presents the description of the Program for the Education of Youths and Adults in the school. Chapter 3 analyzes the demands and contributions of teaching Mathemat
Keywords: educação de adultos; educação de jovens; etnomatemática; education of adults; education of youths; ethnomathematics; Ciências Humanas